Strategi Penerapan Teknologi Informasi dan Dampaknya terhadap Kinerja Keuangan Indogrosir Semarang - Virmansah, Reza Adi; Hendrajaya, Hendrajaya (Mahesa Research Center, 2025)
This article aims to analyze the impact of information technology implementation on operational efficiency and financial performance at Indogrosir Semarang. The focus of the study is on the contribution of information technology systems—such as Enterprise Resource Planning (ERP), Customer Relationship Management (CRM), and Point of Sale (POS)—in improving inventory management efficiency, employee productivity, and marketing strategy effectiveness. This study uses a qualitative approach with a theoretical basis from operational management and management information systems. Data were obtained through direct observation, interviews with management, and analysis of financial reports before and after technology implementation. The results of the study indicate that the implementation of information technology optimizes the restocking process, reduces stock errors, and accelerates sales transactions. On the financial side, there is an increase in net profit margin, operational cost efficiency, and financial report accuracy. However, the implementation process also faces challenges in the form of high initial investment costs, employee resistance to change, and data security risks. This study contributes to the development of practices in operational management and information systems, especially in the context of digital transformation in the wholesale retail sector. In addition, these findings can be a reference for other companies that want to adopt similar technology systems. The limitations of this research lie in the qualitative approach which is contextual in nature, so that the results cannot be generalized widely without additional studies in other companies with different characteristics.